Oxide layer growth on nickel-base alloy surfaces in high temperature water and in O2 studied by ToF-SIMS with isotopic tracers. (December 2018) - Voyshnis, S.; Seyeux, A.; Zanna, S.; Martin-Cabanas, B.; Couvant, T.; Marcus, P.
Highlights: The oxidation of an Alloy 600 in high pressure and high temperature water up to 100 h at 300 °C was investigated by ToF-SIMS. The passive layer is duplex with an inner oxide film that evolves from Cr2 O3 towards NiCr2 O4 with increasing oxidation time. Further oxidation in isotopic 18 O2 of a pre-oxidized in high temperature water Alloy 600 sample evidences the inward diffusion of 18 O species. An appropriate solid state diffusion model was used to estimate the apparent diffusion coefficient (Dapp ) of O species in the growing oxide. Dapp drastically decreases with the oxidation time due to the modification of the chemical composition of the oxide from Cr2 O3 towards NiCr2 O4 . Abstract: Alloy 600 oxidation in high temperature water was investigated by ToF-SIMS. The passive layer formed is duplex with an inner oxide that evolves from Cr2 O3 towards NiCr2 O4 with increasing oxidation time and an outer layer rich in Fe-oxide and Ni hydroxide. Further oxidation in isotopic 18 O2 of a pre-oxidized in high temperature water Alloy 600 was then performed in the ToF-SIMS chamber. It reveals that (i) diffusion of 18 O species is the governing ion transport mechanisms in the oxide and (ii) the apparent diffusion coefficient of O species decreases with the modification of the inner oxide from Cr2 O3 towards NiCr2 O4 .